Hubungan Kohesivitas Keluarga dan Kematangan Karir Siswa Remaja - Jalal, Novita Maulidya (Indo-MathEdu Intellectuals Journal, 2024)
Adolescent students are in a phase of a critical period in individual development, where students are beginning to be required to be able to make important decisions regarding the future, including decisions regarding careers. The purpose of this study is to determine the relationship between family cohesiveness and career maturity of adolescent school students. The research method used is library research or literature research. This study uses data obtained from primary sources, namely journals and scientific articles related to family cohesiveness and adolescent career maturity. Data were obtained using 5 scientific articles. Data analysis was carried out using content analysis techniques. The research results show that family cohesiveness has an important role in supporting students' career maturity. Families that have close emotional relationships and open communication can provide a sense of security and confidence to teenagers, which influences their ability to recognize their own potential and make career-related decisions. Emotional, social and practical support from the family helps students to explore career options more openly and maturely. The implications of this research can be used by parents in supporting teenagers to make decisions regarding life